Self-cleaning textile and preparation method thereof
By modifying the polyacrylonitrile fabric with amidoxime, mixing the quantum dot-enhanced Cu2O with nanoTiO2 hydrosol, loading it on the modified PAN fabric, combining traditional rolling and baking technology, textiles with high photocatalytic efficiency and self-cleaning ability are prepared, solving the problem of easy deactivation of Cu2O photocatalysts and difficult to recover sludge, and achieving efficient and environmentally friendly self-cleaning textiles.
Patent Information
- Application Number
- CN202411702718.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-21
AI Technical Summary
During use, the existing photocatalyst material Cu2O is prone to inactivate due to the recombination of electron pairs with holes, and its powdery form will form difficult to recover sludge when dealing with contamination, limiting its application efficiency and sustainability.
Textiles with high photocatalytic efficiency and self-cleaning ability were prepared by modifying polyacrylonitrile (PAN) fabrics and mixing quantum dot-enhanced Cu2O with nanoTiO2 hydrosols, loading them on the modified PAN fabrics, and combining traditional rolling and baking processes.
It realizes that the photocatalyst is not easy to deactivate, has high photocatalytic efficiency, significant self-cleaning effect, wide application conditions, and the preparation process is energy-saving and environmentally friendly, suitable for industrial production.
Smart Images

Figure CN119663627A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a textile and a preparation method thereof, in particular to a self-cleaning textile and a preparation method thereof, and belongs to the field of textiles. Background Art
[0002] Photocatalysis is a way of using light energy to transform substances. Under the combined action of light and catalysts, substances undergo chemical reactions. It can be used in the fields of environmental pollution control, development of renewable energy, and material synthesis. Photocatalysis is a new technology for rapid and efficient degradation and removal of persistent organic pollutants, and is widely used in wastewater treatment and purification technology. Under light conditions, the surface of the photocatalyst produces hydroxyl or superoxide free radicals with strong oxidizing properties, which can cause various pollutant molecules to undergo oxidation reactions and mineralize to form non-toxic and harmless inorganic small molecules such as CO2 and H2O. Common semiconductor oxide catalyst materials include titanium dioxide (TiO2) and cuprous oxide (Cu2O), which have the advantages of strong oxidizing ability, high catalytic activity, and good stability. However, Cu2O has two significant defects as a photocatalyst: 1. Electron pairs are easy to recombine with holes, which greatly limits its photocatalytic efficiency; 2. Cu2O is in powder form, and when treating persistent organic pollutants in water, a large amount of sludge will be formed, which is difficult to recycle and reuse. The second defect can be overcome by loading the photocatalyst onto the textile, which can not only reduce the loss of the photocatalyst, but also enable the textile to obtain self-cleaning properties through photocatalysis.
[0003] Polyacrylonitrile (PAN) is a polymer compound with good weather resistance and sunlight resistance, and also has good tolerance to chemical reagents. Polyacrylonitrile is mainly used to make synthetic fibers, which can replace wool or be blended with wool to make wool fabrics. Although its strength is not high, and its wear resistance and fatigue resistance are also poor, the defects have been overcome by composite or modified methods, and PAN has various excellent properties. Patent application CN112458621A discloses a supported nano-cuprous oxide-nanofiber composite material and its preparation method, which effectively loads nano-cuprous oxide on a nanofiber membrane, has a stable structure, is easy to recycle, and does not cause secondary pollution; at the same time, the advantages of the nanofiber membrane such as porous and large specific surface area are effectively utilized, which has a positive significance for further improving the adsorption photocatalytic performance of the nano-composite fiber, and can be used to make air and wastewater purifier filters. However, the composite material focuses on the effect of Cu2O morphology differences on photocatalysis, and fails to solve the problem that electron pairs are easy to recombine with holes, causing photocatalyst deactivation. Moreover, the electrospinning method adopted in this technical solution causes part of the Cu2O to be encapsulated inside the fiber, so that the photocatalytic effect cannot be fully exerted. In addition, the light response range of the fabric made by using only Cu2O as a photocatalyst is also relatively limited. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a self-cleaning polyacrylonitrile fabric and a preparation method thereof, wherein the photocatalyst loaded on the fabric is not easily deactivated, can fully exert the photocatalytic effect, and has a wider light response range.
[0005] Technical solution: The method for preparing the self-cleaning textile of the present invention comprises the following steps: Step 1: Modify PAN fabric with amidoxime; Step 2: Preparation of quantum dot enhanced Cu2O; Step 3: preparing nano-TiO2 hydrosol; Step 4: Add the Cu2O / quantum dot particles prepared in step 2 to the nano-TiO2 hydrosol prepared in step 3 and mix them, immerse the modified PAN fabric prepared in step 1 therein, keep it for a period of time, and then treat the fabric by a padding-prebaking-baking process, and obtain a self-cleaning textile after washing and drying.
[0006] The technical solution first modifies the surface of PAN fiber with amidoxime, and then loads the Cu2O / TiO2 / quantum dot nanocomposite material on the surface through the traditional dyeing and finishing industrial rolling and baking process, and finally obtains textiles with self-cleaning ability. Since the amidoxime group increases the active sites on the PAN fiber, the Cu2O / TiO2 / quantum dot nanocomposite material can be firmly loaded on the fiber surface, so that each photocatalyst ion can fully play its role, thereby improving the photocatalytic efficiency. In addition, the technical solution reduces the recombination of electron pairs and holes by doping TiO2 and quantum dots, and solves the problem of easy inactivation of Cu2O photocatalytic performance by virtue of the good acceptance of electrons and large electron capacity of both. In addition, the technical solution combines Cu2O that absorbs visible light with TiO2 that absorbs ultraviolet light, so that the self-cleaning textile obtained can respond to a wider spectrum than similar products loaded with a single type of photocatalyst. Loading Cu2O on PAN fabric can also increase the pH application range, so that the obtained self-cleaning textile can play a catalytic degradation role under neutral or even alkaline conditions. At the same time, the rolling-baking-baking finishing method adopted by the technical solution is fast and efficient, and the treatment of the surface-loaded Cu2O / TiO2 / quantum dot nanocomposite material can be mostly carried out under low temperature conditions, which not only reduces the processing cost, but is also simple, efficient and safe, and is conducive to the mass production of the self-cleaning textiles. Compared with the prior art, the preparation time of the technical solution is shorter, the process is easy to control and no wastewater is generated, which is both energy-saving and environmentally friendly and conducive to the reuse of resources.
[0007] Preferably, in step 4, the solid-liquid ratio of the Cu2O / quantum dot particles to the nano-TiO2 hydrosol is 3-10:50-200, and the unit of the solid-liquid ratio is g / mL; the mass ratio of the Cu2O / quantum dot particles to the modified PAN fabric is 3-10:3-8.
[0008] Preferably, in step 4, the condition for maintaining the temperature for a period of time is a 50-80° C. water bath for 10-60 min.
[0009] Preferably, in step 4, the padding-prebaking-baking process is achieved by a uniform padder-baking machine combined system, and the conditions are: two dips and two pads, padding rate 75%-80%, prebaking 80-100°C, treatment time 3-10 min; baking temperature 150-200°C, treatment time 0.5-2 min.
[0010] Preferably, in step 1, the amidoxime modification method is to immerse the PAN fabric in a first aqueous solution containing Na2CO3 and soap flakes, treat it in a water bath, wash it with water, and then immerse it in a second aqueous solution containing hydroxylamine hydrochloride and NaOH, mix it, wash it with water, and dry it to obtain the modified PAN fabric.
[0011] The free hydroxylamine molecules released by hydroxylamine hydrochloride and NaOH react with PAN fibers to convert the cyano groups in PAN fibers into amidoxime groups (H2N-C=N-OH). The relevant reaction equation is shown below:
[0012] Preferably, the PAN fabric treatment bath ratio is 1:50-1:100, the concentration ratio of Na2CO3 to soap flakes in the first aqueous solution is 1-3:1-5, and the concentration ratio of hydroxylamine hydrochloride to NaOH in the second aqueous solution is 5-25:1-10. The reaction conditions of PAN fabric and the first aqueous solution are 50-100°C, 30-60 min; the reaction conditions of PAN fabric and the second aqueous solution are 60-80°C, 30-60 min.
[0013] Preferably, in step 2, the method for preparing quantum dot enhanced Cu2O is to add the Cu2SO4 solution dropwise to the NaOH solution, add polyvinyl pyrrolidone (PVP) and ultrasonicate after mixing, then add the glucose solution and ultrasonicate, filter, wash the obtained solid with ethanol and dry it to obtain Cu2O / quantum dot particles. The preferred reaction conditions of this method are: NaOH aqueous solution concentration 1-3 mol / L, volume 100-300 ml; Cu2SO4 aqueous solution concentration 0.1-0.5 mol / L, volume 100-300 ml; PVP dosage 3-10 g, ultrasonic treatment conditions 40-60 kHz, 100-160 W, 40-100 min; glucose aqueous solution concentration 1-3 mol / L, volume 100-200 ml.
[0014] Preferably, in step 3, the method for preparing nano-TiO2 hydrosol is to mix butyl titanate and anhydrous ethanol, then drip into a hydrochloric acid aqueous solution and stir, and seal and stand to form a nano-TiO2 hydrosol. The preferred reaction conditions of the method are: the amount of butyl titanate is 10-30 g, the amount of anhydrous ethanol is 30-80 g, the pH of the hydrochloric acid aqueous solution is 1-2, the dripping speed is 1-2 drops per second, the stirring time is 60-150 min, and the aging (sealed and standing) is 3-7 days.
[0015] The self-cleaning textile of the present invention is obtained by the above preparation method.
[0016] The self-cleaning textile has the advantages of high photocatalytic efficiency, good self-cleaning effect, durability and wide application conditions.
[0017] The application of the self-cleaning textile of the present invention is the application of the self-cleaning textile in sewage treatment.
[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. The preparation method of the self-cleaning textile is time-saving, low-cost, easy to control, energy-saving and environmentally friendly, and has the advantages of simplicity, efficiency and safety, and is suitable for industrial production; 2. The photocatalyst loaded on the self-cleaning textile is not easy to deactivate, has high photocatalytic efficiency, good self-cleaning effect, durability and a wide range of applicable conditions, and is suitable for fields such as sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the self-cleaning effect of 6 self-cleaning textiles in a specific embodiment; Figure 2 Schematic diagram of the reuse performance of three self-cleaning textiles in a specific implementation manner. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0021] Example 1: A method for preparing a self-cleaning textile This embodiment obtains a self-cleaning textile by the following method: Step 1: PAN fabric was immersed in an aqueous solution containing 1.0 g / L Na2CO3 and 2.0 g / L soap flakes at a bath ratio of 1:50 and treated in a 60 ℃ water bath for 30 min. After being taken out, it was thoroughly washed with distilled water to remove residual additives and dust during the fabric processing and use.
[0022] Step 2: Immerse 1.0 g of the PAN fabric pretreated as above into 50 mL of an aqueous solution containing 30 g / L hydroxylamine hydrochloride and 10 g / L NaOH, and carry out coordination reaction at 70 °C under stirring conditions. After 30 min, take out the fabric and wash it repeatedly with distilled water until it is neutral, and dry it to obtain the modified PAN fabric.
[0023] Step 3: Prepare 150 ml of NaOH aqueous solution (1.0 mol / L), add 150 ml of Cu2SO4 aqueous solution (0.1 mol / L) dropwise therein, stir thoroughly and add 6 g of PVP, and ultrasonically treat for 30 min (150 W, 40 kHz); add 100 ml of glucose aqueous solution (1.0 mol / L) therein, and continue ultrasonically treating for 60 min; filter the above mixture, wash the obtained solid sample with ethanol several times, and obtain Cu2O / quantum dot particles after drying in an oven.
[0024] Step 4: Mix 15 g of butyl titanate and 30 g of anhydrous ethanol thoroughly, and drip into a pH 1.5 hydrochloric acid aqueous solution at a rate of 1.5 drops per second under room temperature and stirring conditions. Continue stirring for 1 hour after dripping; seal and let stand for several days until it forms a translucent nano-TiO2 hydrosol.
[0025] Step 5: Take 3 g of Cu2O / quantum dot particles and add them to 100 ml of nano-TiO2 aqueous sol. After fully stirring, 5 g of modified PAN fabric is immersed in it and kept at 60 ℃ for 20 min. Use a uniform padder-dryer combined system to treat the modified PAN fabric through a process of impregnation (two impregnations and two rollings, liquid rolling rate: 75%-80%) - pre-baking (80 ℃×4.5 min) - baking (180 ℃×1.5 min). Use distilled water to repeatedly wash and dry to obtain Cu2O / TiO2 / quantum dot-PAN fabric.
[0026] Example 2: A method for preparing a self-cleaning textile This embodiment obtains a self-cleaning textile by the following method, which is different from the embodiment 1 in that only Cu2O, a photocatalyst, is used instead of TiO2. The specific steps are as follows: Step 1-3: Same as Step 1-3 of Example 1.
[0027] Step 4: Take 3 g of Cu2O particles and add them to 100 ml of 30% ethanol aqueous solution (pH 1.5). After fully stirring, 5 g of modified PAN fabric is immersed in it and kept at 60 °C for 20 min. Use a uniform padder-dryer combined system to treat the modified PAN fabric through a process of padding (two dips and two pads, padding rate: 75%-80%) - pre-baking (80 °C × 4.5 min) - baking (180 °C × 1.5 min). Use distilled water to repeatedly wash and dry to obtain Cu2O / quantum dot-PAN fabric.
[0028] Example 3: A method for preparing a self-cleaning textile This embodiment obtains a self-cleaning textile by the following method, which is different from the embodiment 1 in that only TiO2, a photocatalyst, is used instead of Cu2O. The specific steps are as follows: Steps 1-3: Same as steps 1, 2, and 4 of Example 1.
[0029] Step 4: Immerse 5 g of modified PAN fabric in 100 ml of nano-TiO2 aqueous sol and keep it at 60 ℃ for 20 min; use a uniform padder-dryer combined system to treat the modified PAN fabric through a process of immersion padding (two immersions and two paddings, liquid padding rate: 75%-80%) - pre-baking (80 ℃ × 4.5 min) - baking (180 ℃ × 1.5 min); repeatedly wash with distilled water and dry to obtain TiO2-PAN fabric.
[0030] Example 4: A method for preparing a self-cleaning textile This embodiment obtains a self-cleaning textile by the following method, which is different from the embodiment 1 in that Cu2O particles are used to replace Cu2O / quantum dot particles. The specific steps are as follows: Step 1-2: Same as step 1-2 of Example 1.
[0031] Step 3: Prepare 150 ml of NaOH aqueous solution (1.0 mol / L), add 150 ml of Cu2SO4 aqueous solution (0.1 mol / L) dropwise into it, stir thoroughly and add 6 g of PVP, and ultrasonically treat for 30 min (150 W, 40 kHz); after filtering, wash the obtained solid sample with ethanol several times, and obtain Cu2O particles after drying in an oven.
[0032] Step 4-5: Same as step 4-5 of Example 1, except that the Cu2O / quantum dot particles are replaced with Cu2O particles.
[0033] Example 5: A method for preparing a self-cleaning textile This embodiment obtains a self-cleaning textile by the following method, which is different from the embodiment 1 in that the PAN fabric is not modified with amidoxime. The specific steps are as follows: Steps 1-3: Same as steps 1, 3, and 4 of Example 1.
[0034] Step 4: Same as step 5 of Example 1, except that the modified PAN fabric is replaced with unmodified PAN fabric.
[0035] Comparative Example 1: A method for preparing a self-cleaning textile This comparative example obtains a self-cleaning textile by the following method, which is mainly different from Example 1 in that an electrospinning method is used to replace a rolling-baking-baking finishing method. The specific steps are as follows: Step 1-2: The same as step 1-2 of Example 1, except that the PAN fabric is replaced with PAN microparticles that can be used for electrospinning.
[0036] Step 3-4: Same as Step 3-4 of Example 1.
[0037] Step 5: 0.5% of the Cu2O / TiO2 / quantum dot composite and 13% of the amidoxime-modified PAN particles were placed in N,N-dimethylacetamide (DMAc) to prepare a uniform Cu2O / TiO2 / quantum dot-PAN spinning solution.
[0038] Step 6: Place the Cu2O / TiO2 / quantum dot-PAN spinning solution in an electrospinning machine, adjust the distance between the needle and the receiver to 20 cm and the spinning voltage to 15 KV, collect it on a receiving roller wrapped with a non-woven fabric, and obtain a Cu2O / TiO2 / quantum dot-PAN electrospinning fiber membrane.
[0039] Step 7: Dry the Cu2O / TiO2 / quantum dot-PAN electrospun fiber membrane in vacuum at 60°C for 10 h.
[0040] Performance Test 1: Self-cleaning ability of textiles The degradation effect of Reactive Red 195 on the fabrics obtained in Examples 1-5 and Comparative Example 1 was tested.
[0041] Test principle: Before the test, the Reactive Red 195 aqueous solution is pink. As the degradation process continues, the color of the Reactive Red 195 aqueous solution gradually fades until it fades completely. The fading degree of the dye is measured throughout the process to evaluate the photocatalytic ability of the fabric (i.e. self-cleaning ability).
[0042] Detection method: First, 0.25 g of the self-cleaning textile of the present invention was soaked in 50 mL of 0.05 mM / L Reactive Red 195 aqueous solution. Then, an appropriate amount of 0.003 mol / L H2O2 was added thereto. The mixed solution was irradiated with a mercury lamp at a temperature of 25°C (the radiation intensity of the mercury lamp was: ultraviolet light (365 nm): 457 μW / cm 2 , visible light (400-1000 nm): 4987 μW / cm 2 ) for oxidative degradation reaction. During the reaction, a small amount of Reactive Red 195 aqueous solution was taken out at regular intervals, and the absorbance value of Reactive Red 195 at the maximum absorption wavelength (521 nm) was measured using a visible spectrophotometer to calculate the decolorization rate (D%) of the dye. The effect of the fabrics obtained in Examples 1-5 and Comparative Example 1 on degradation of Reactive Red 195 is shown in the figure. Figure 1 shown.
[0043] The main differences between the preparation methods of Examples 1-5 and Comparative Example 1 are shown in Table 1.
[0044] Table 1 Comparison of technical features of Examples 1-5 and Comparative Example 1 name Fabric modification <![CDATA[Cu2O]]> <![CDATA[Cu2O / Quantum Dots]]> <![CDATA[TiO2]]> Photocatalyst loading process Example 1 √ √ √ Industrial rolling-baking-roasting Example 2 √ √ Industrial rolling-baking-roasting Example 3 √ √ Industrial rolling-baking-roasting Example 4 √ √ √ Industrial rolling-baking-roasting Example 5 √ √ Industrial rolling-baking-roasting Comparative Example 1 √ √ √ Electrospinning from Figure 1 It can be seen that the degradation effect of the textile obtained in Example 1 is the best. The textile obtained in Example 2 can only absorb part of the visible light, and the textile obtained in Example 3 can only absorb part of the visible light, so their degradation effects are not ideal. The textile obtained in Example 4 does not have the support of quantum dots, Cu2O is easily deactivated, and visible light cannot be fully utilized, so its D% value is lower than that in Example 1. The textile obtained in Example 5 uses unmodified PAN fiber, and the surface of the fiber lacks binding sites for the photocatalyst, so the amount of Cu2O / quantum dots / TiO2 loaded is small, and the D% value is low. The photocatalyst of the textile obtained in Comparative Example 1 is coated inside the fiber, and only a small amount of photocatalyst is exposed on the fiber surface, so the degradation effect is much lower than that in Example 1.
[0045] Performance Test 2: Durability of Textile Self-Cleaning Ability The durability of the self-cleaning ability of the textiles obtained in Example 1, Example 5 and Comparative Example 1 was tested.
[0046] Detection method: After the dye photocatalytic oxidation degradation experiment, the self-cleaning textile was taken out of the reaction solution, placed in a solution of water and ethanol mixed in a ratio of 1:1, and ultrasonically cleaned for 30 minutes under stirring, then taken out and dried. Then, the textile was put back into the same concentration of Reactive Red 195 aqueous solution and the oxidation degradation reaction was carried out again using the same method. The reusability of the catalyst was evaluated by comparing the changes in the dye decolorization rate (D%) during repeated use.
[0047] from Figure 2 It can be seen that the durability of the textile obtained in Example 1 is the best, and it still has good degradation ability after five washings and dryings. The textile obtained in Example 5 uses unmodified PAN fiber as a substrate, so the photocatalytic composite is not firmly combined with the fabric, and it is easy to fall off during the reuse process, so that its photocatalytic effect is gradually reduced. The reusability of the textile obtained in Comparative Example 1 is relatively stable, but its defect is that Cu2O / quantum dots / TiO2 can produce highly reactive free radicals on its surface after being excited by light, so that the photocatalytic effect can be exerted. And Example 1 can overcome this defect well, because Cu2O / quantum dots / TiO2 are all exposed on the fiber surface, and PAN can firmly fix Cu2O / quantum dots / TiO2 on the fiber surface after being modified by amidoxime, so the photocatalytic performance and reuse performance of Example 1 are relatively good. In addition, the electrospinning method in Comparative Example 1 is limited to obtaining small samples for experiments in the laboratory, and it is difficult to achieve large-scale industrial production, while the loading method used in Example 1 can be industrialized and continuously produced.
Claims
1. A method for preparing a self-cleaning textile, characterized in that: The following steps are involved: Step 1: Modify PAN fabric with amidoxime; Step 2: Preparation of quantum dot enhanced Cu2O; Step 3: preparing nano-TiO2 hydrosol; Step 4: Add the Cu2O / quantum dot particles prepared in step 2 to the nano-TiO2 hydrosol prepared in step 3 and mix them, immerse the modified PAN fabric prepared in step 1 therein, keep it for a period of time, and then treat the fabric by a padding-prebaking-baking process, and obtain a self-cleaning textile after washing and drying.
2. The preparation method according to claim 1, characterized in that: In step 4, the solid-liquid ratio of the Cu2O / quantum dot particles to the nano-TiO2 hydrosol is 3-10:50-200, and the unit of the solid-liquid ratio is g / mL; the mass ratio of the Cu2O / quantum dot particles to the modified PAN fabric is 3-10:3-8.
3. The preparation method according to claim 1, characterized in that: In step 4, the condition for maintaining the mixture for a period of time is a 50-80° C. water bath for 10-60 min.
4. The preparation method according to claim 3, characterized in that: In step 4, the padding-prebaking-baking process is achieved by a uniform padder-baking machine combined system, and the conditions are: two dips and two pads, a padding rate of 75%-80%, a prebaking temperature of 80-100°C, and a treatment time of 3-10 min; a baking temperature of 150-200°C and a treatment time of 0.5-2 min.
5. The preparation method according to claim 1, characterized in that: In step 1, the amidoxime modification method is to immerse the PAN fabric in a first aqueous solution containing Na2CO3 and soap flakes, treat it in a water bath, wash it with water, and then immerse it in a second aqueous solution containing hydroxylamine hydrochloride and NaOH, mix it, wash it with water, and dry it to obtain the modified PAN fabric.
6. The preparation method according to claim 5, characterized in that: The PAN fabric treatment bath ratio is 1:50-1:100, the concentration ratio of Na2CO3 to soap flakes in the first aqueous solution is 1-3:1-5, and the concentration ratio of hydroxylamine hydrochloride to NaOH in the second aqueous solution is 5-25:1-10.
7. The preparation method according to claim 1, characterized in that: In step 2, the method for preparing quantum dot enhanced Cu2O is to add the Cu2SO4 solution dropwise to the NaOH solution, add polyvinyl pyrrolidone and sonicate after mixing, then add the glucose solution and sonicate, filter, wash the obtained solid with ethanol and dry it to obtain Cu2O / quantum dot particles.
8. The preparation method according to claim 1, characterized in that: In step 3, the method for preparing the nano-TiO2 hydrosol is to mix butyl titanate and anhydrous ethanol, then drip into a hydrochloric acid aqueous solution and stir, and seal and let stand until the nano-TiO2 hydrosol is formed.
9. A self-cleaning textile obtained according to the preparation method of claim 1.
10. Use of the self-cleaning textile according to claim 9 in sewage treatment.
Citation Information
Patent Citations
Supported nano cuprous oxide-nanofiber composite material and preparation method thereof
CN112458621A